Analysis The Consistency Between The Tariff And The Exchange Rate And Their Reflection On The Trade Balance In Iraq - عبد اللطيف عماد محمد; محي براق حسين (Journal of Economics and Administrative Sciences, 2019)
The trade balance is considered as a way to join the national economy with the world, So it is the mirror that reflect the economic center of the country and it is point to competitive ability of it, The tariff and the exchange rate perform a great role to motivate the domestic production and improve the trade balance if we direct them to achieve the same purpose. The Iraqi economic has trade balance which achieve overabundant during the years of studying because of the oil exports, while the other exports represent a small percentage it is hardly remember, and expansion in imports from other side causes exhaustion in oil revenues, and this make the trade balance in permanent shortage and raising in business exposure and put the country in a very difficult situation in case of changing in its oil exports prices or quantity. The negative consistency between the tariff and exchange rate which appear through the weakness of the tariff contribution and the absence of it is role, and rising of exchange rate from other hand is one of the reasons of the Iraqi trade balance shortage. The main conclusion that the researcher worked out that assumption activation of tariff and reducing the Iraqi dinar rate exchange refer clearly to successful consistency between these two variable whereas both of them lead to a rise in the value of imports which motivate the domestic production instead of it and increasing the exports to improve the trade balance. In the end the researcher recommends first of all that tariff must be levied on goods that can be produced domestically at a higher rate than goods that are not capable of producing them, To stimulate the front and back linkages of these industries, and when there is elastic production that means it is a chance to reduce the exchange rate which reflect positively on the Iraqi trade balance.